A case study into English classroom assessment practices in three primary schools in Hanoi: Implications for developing a contextualized formative assessment practice framework - Anh, Phạm Lan (VNU Journal of Foreign Studies, 2013)
Abstract : Formative assessment (FA) has emerged as a lever to raise the quality of the teaching/learning process. While FA is claimed to enhance teaching and learning gains, the implementation of FA in particular settings has not yet been as successful as expected due to a lack of proper frameworks to guide the practice for optimal results. This article attempts to propose some principles toward developing a contextualized formative assessment practice framework (CFAPF), informed by a   case study into classroom assessment practices of teachers of English in three primary schools in Hanoi, Viet Nam. First, several studies on formative assessment practices (FAPs) in Western countries and Hong Kong are reviewed, followed by the rationale for a much needed contextualized framework for the researched classrooms in Hanoi.  Next, the methodology employed in the case study is depicted. Then, based on the major findings extracted from the observed classroom assessment process, on evidence of formative assessment elements embedded in daily teaching strategies, as well as threats to FA, such principles for the suggested framework as particularity , practicality and learning promotion are built up. Finally, the article concludes with an emphasis on some key points to be considered the necessary and sufficient conditions for the successful application of the framework, namely, the importance of daily lesson planning, the simultaneous focus on the three components of FA (i.e., identification of student learning, feedback and feedforward to that learning, and consequent remedies), and considerations of the actual teaching and learning contexts . Keywords : Assessment, Assessment for Learning (AFL), Formative Assessment (FA), Teacher Assessment Practice (TAP), Teaching English to Young Learners (TEYL), English as an Additional Language (EAL), English Language Teaching (ELT).